The Tip of the Iceberg: On the Roles of Regulatory Small RNAs in the Virulence of Enterohemorrhagic and Enteropathogenic Escherichia coli - Bhatt, Shantanu; Egan, Marisa; Jenkins, Valerie; Muche, Sarah; El-Fenej, Jihad (Frontiers in Cellular and Infection Microbiology, 2016)
Enterohemorrhagic and enteropathogenic Escherichia coli are gastrointestinal pathogens that disrupt the intestinal microvilli to form attaching and effacing (A/E) lesions on infected cells and cause diarrhea. This pathomorphological trait is encoded within the pathogenicity island locus of enterocyte effacement (LEE). The LEE houses a type 3 secretion system (T3SS), which upon assembly bridges the bacterial cytosol to that of the host and enables the bacterium to traffic dozens of effectors into the host where they hijack regulatory and signal transduction pathways and contribute to bacterial colonization and disease. Owing to the importance of the LEE to EHEC and EPEC pathogenesis, much of the research on these pathogens has centered on its regulation. To date, over 40 proteinaceous factors have been identified that control the LEE at various hierarchical levels of gene expression. In contrast, RNA-based regulatory mechanisms that converge on the LEE have only just begun to be unraveled. In this minireview, we highlight major breakthroughs in small RNAs (sRNAs)-dependent regulation of the LEE, with an emphasis on their mechanisms of action and/or LEE-encoded targets.